2014 IEEE 64th Electronic Components and Technology Conference (ECTC) 2014
DOI: 10.1109/ectc.2014.6897525
|View full text |Cite
|
Sign up to set email alerts
|

Novel TSV process technologies for 2.5D/3D packaging

Abstract: 2.5D silicon interposers" and "Hetero 3D stacked" technology for high-performance LSI are gathering the most attention from now on. These technologies can solve interconnection problems using TSV (Through Silicon Via) to electrically connect stacked each function devises. 2.5D and hetero-3D Si integration has great advantages over conventional 2D devices such as high packaging density, small wire length, high-speed operation, low power consumption, and high feasibility for parallel processing. But, the radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Through silicon via (TSV) technology has become attractive as a potential solution to further extend Moore's law through vertical connection to realize boosts in system performance and integration density while maintaining acceptable fabrication costs using wafer-level packaging [5]. Various studies have shown the process readiness of 2.5D Si interposer [6][7][8] or embedded TSV as wide I/O [9], although low-volume TSV technology is from via-last wafer-level packaging, which uses TSV with partial metal filling [10,11]. Although this is a more cost-effective wafer-level packaging solution, it is not suitable for implementation in applications such as sensors, RF, and power devices that require good signal quality, robust reliability, and acceptable fabrication costs under squeezed package sizes (both for planar format and vertical thickness).…”
Section: Introductionmentioning
confidence: 99%
“…Through silicon via (TSV) technology has become attractive as a potential solution to further extend Moore's law through vertical connection to realize boosts in system performance and integration density while maintaining acceptable fabrication costs using wafer-level packaging [5]. Various studies have shown the process readiness of 2.5D Si interposer [6][7][8] or embedded TSV as wide I/O [9], although low-volume TSV technology is from via-last wafer-level packaging, which uses TSV with partial metal filling [10,11]. Although this is a more cost-effective wafer-level packaging solution, it is not suitable for implementation in applications such as sensors, RF, and power devices that require good signal quality, robust reliability, and acceptable fabrication costs under squeezed package sizes (both for planar format and vertical thickness).…”
Section: Introductionmentioning
confidence: 99%
“…A negative profile has a bottom width that is larger than its top width, and as a result a large part of the feature will be shadowed by the top opening of the profile. The straight profile has vertical 'cliff edges' which can cause difficulties obtaining a consistent film thickness and deposited material will naturally gravitate towards the bottom of the feature causing inconsistent film thicknesses [26]. One of the largest defects resulting from the positive etch process is the formation of a feature at the top of the profile that is often known as an 'overhang', 'undercut' or 'lateral etching'; where the area directly below the mask is narrower than the widest dimension of the TSV structure as shown in Figure 7b.…”
Section: Tsv Profile Undercut Formationmentioning
confidence: 99%
“…Figure 10: Effect of Mask Profile on Undercut [26] was drawn down the chamfer angle and continued until the line intersected the feature sidewall it corresponded with the bottom of the lateral etching region. To prove this effect researchers have deliberately created a chamfered feature at the mask hole edge and ran the same etch process on the sample.…”
Section: Undercut Level Comparisonmentioning
confidence: 99%